The structure and petrology of the George granite plutons and the invaded pre-Cape sedimentary rocks - Potgieter, C. T.(Coenraad T.),1906- (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1949.